Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Dalam Perspektif Islam (Studi Kasus Bank Muamalat Balai Kota Medan) - Nasution, Rahmi Andini; Mujiatun, Siti (Universitas Labuhanbatu, 2024)
This research was conducted with the aim of analyzing the effect of leadership style and work motivation on employee performance in an Islamic perspective (a case study of bank muamalat city hall of Medan). The research method used in this study is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classic assumption test, multiple linear regression test, hypothesis test and determination test. Based on the results of the study, it was shown that the variable t (partial) test results showed that the significant value of leadership style (X1) on employee performance at Bank Muamalat Balai Kota Medan (Y) was 0.001 <0.05 and the value of t count was 4.301 > t tableÂ 2,012 ,so Ho1 is rejected and Ha1 is accepted. As for seeing the magnitude of the influence of leadership style on employee performance at bank muamalat, look at the